Apoptosis inhibitor 5 is an endogenous inhibitor of caspase‐2. (23rd March 2017) - Imre, Gergely; Berthelet, Jean; Heering, Jan; Kehrloesser, Sebastian; Melzer, Inga Maria; Lee, Byung Il; Thiede, Bernd; Dötsch, Volker; Rajalingam, Krishnaraj
Abstract: Caspases are key enzymes responsible for mediating apoptotic cell death. Across species, caspase‐2 is the most conserved caspase and stands out due to unique features. Apart from cell death, caspase‐2 also regulates autophagy, genomic stability and ageing. Caspase‐2 requires dimerization for its activation which is primarily accomplished by recruitment to high molecular weight protein complexes in cells. Here, we demonstrate that apoptosis inhibitor 5 (API5/AAC11) is an endogenous and direct inhibitor of caspase‐2. API5 protein directly binds to the caspase recruitment domain (CARD) of caspase‐2 and impedes dimerization and activation of caspase‐2. Interestingly, recombinant API5 directly inhibits full length but not processed caspase‐2. Depletion of endogenous API5 leads to an increase in caspase‐2 dimerization and activation. Consistently, loss of API5 sensitizes cells to caspase‐2‐dependent apoptotic cell death. These results establish API5/AAC‐11 as a direct inhibitor of caspase‐2 and shed further light onto mechanisms driving the activation of this poorly understood caspase. Synopsis: Caspase‐2, despite being evolutionarily conserved, is still a poorly understood initiator caspase that is activated by CARD domain‐mediated dimerization. This study identifies apoptosis inhibitor 5 (AIP5) as an endogenous inhibitor and elucidates the molecular mechanism of inhibition. API5 is an endogenous inhibitor of caspase‐2. API5 directly binds to the CARD domain of caspase‐2 and prevents dimerization. API5 loss sensitizes cells to caspase‐2‐dependent apoptotic cell death. Abstract : Initiator caspases depend on dimerization for their activation. API5 directly binds to the CARD domain of caspase‐2 and prevents its dimerization.